Linking Bacterial Endophytic Communities to Essential Oils: Clues from Lavandula angustifolia Mill. (26th May 2014) - Emiliani, Giovanni; Mengoni, Alessio; Maida, Isabel; Perrin, Elena; Chiellini, Carolina; Fondi, Marco; Gallo, Eugenia; Gori, Luigi; Maggini, Valentina; Vannacci, Alfredo; Biffi, Sauro; Firenzuoli, Fabio; et al.
Abstract : Endophytic bacteria play a crucial role in plant life and are also drawing much attention for their capacity to produce bioactive compounds of relevant biotechnological interest. Here we present the characterisation of the cultivable endophytic bacteria of Lavandula angustifolia Mill.—a species used since antiquity for its therapeutic properties—since the production of bioactive metabolites from medical plants may reside also in the activity of bacterial endophytes through their direct production, PGPR activity on host, and/or elicitation of plant metabolism. Lavender tissues are inhabited by a tissue specific endophytic community dominated by Proteobacteria, highlighting also their difference from the rhizosphere environment where Actinobacteria and Firmicutes are also found. Leaves' endophytic community resulted as the most diverse from the other ecological niches. Overall, the findings reported here suggest: (i) the existence of different entry points for the endophytic community, (ii) its differentiation on the basis of the ecological niche variability, and (iii) a two-step colonization process for roots endophytes. Lastly, many isolates showed a strong inhibition potential against human pathogens and the molecular characterization demonstrated also the presence of not previously described isolates that may constitute a reservoir of bioactive compounds relevant in the field of pathogen control, phytoremediation, and human health.